2021
DOI: 10.1039/d0py01618g
|View full text |Cite
|
Sign up to set email alerts
|

Design guide of amphiphilic crystalline random copolymers for sub-10 nm microphase separation

Abstract: Sub-10 nm lamellar structures are efficiently constructed by the pendant microphase separation of amphiphilic crystalline random copolymers with broad molecular weight distribution that are obtained from free radical copolymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…So far, polymeric lamellar-structured materials have been prepared using crystalline polymers, 12 , 13 liquid crystalline polymers, 14 17 and block copolymers, 18 20 while reports using amorphous homo- and copolymers remain scarce. 21 , 22 In this context, we have discovered that a series of amorphous homo- and copolymers of alkyl acrylate and alkyl acrylamide form uniaxially oriented lamellar structures via annealing above their glass-transition temperatures ( T g ) under humid conditions (humid annealing). 23 28 During the humid annealing, water molecules adsorb on the hydrophilic amide and ester groups due to the highly humid conditions.…”
Section: Introductionmentioning
confidence: 99%
“…So far, polymeric lamellar-structured materials have been prepared using crystalline polymers, 12 , 13 liquid crystalline polymers, 14 17 and block copolymers, 18 20 while reports using amorphous homo- and copolymers remain scarce. 21 , 22 In this context, we have discovered that a series of amorphous homo- and copolymers of alkyl acrylate and alkyl acrylamide form uniaxially oriented lamellar structures via annealing above their glass-transition temperatures ( T g ) under humid conditions (humid annealing). 23 28 During the humid annealing, water molecules adsorb on the hydrophilic amide and ester groups due to the highly humid conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the size of each structure can be tuned by changing the degree of polymerization. In general, the self-assembled structure size prepared from block copolymers is about a few tens of nanometers and highly segregated block copolymers with low-molecular-weight or block copolymers with complex structures should be synthesized to prepare a sub-10 nm structure. On the other hand, homopolymers and statistical copolymers also form highly oriented lamellae by taking advantage of the crystallinity or liquid crystallinity of the side chains. The lamellar periodicity of homo and statistical copolymer depends on the length of the side chain and is usually approximately a few nanometers. The periodicity is 1 order of magnitude lower than that prepared from block copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Moreover, Terashima et al have reported that amphiphilic random copolymers composed of octadecyl (meth)acrylate and oligo ethylene glycol form lamellar structures via phase separation of the crystallized octadecyl side chains and hydrophilic oligo ethylene glycol side chains. [18,19] They also controlled d values from 5.3 to 6.3 nm by changing comonomer ratio of octadecyl (meth)acrylate and oligo ethylene glycol. These reports suggest that it is possible to create a few nanometer size self-assembled structures in homopolymers and random copolymers by using segregation between the main chains and side chains or comonomers.…”
Section: Introductionmentioning
confidence: 99%